DEVELOPMENT OF READING LEARNING VIDEOS FOR ELEMENTARY SCHOOL STUDENTS - Lestari, Ni Putu Yeni; Wibawa, I Made Citra; Margunayasa, I Gede (Universitas Pendidikan Ganesha, 2021)
Learning to read during learning activities from home is less effective because reading learning media are difficult to find. This study aims to create a reading learning video development for first-grade elementary school students and develop a reading learning video for first-grade elementary school students whose validity is tested using the ADDIE model. However, due to limited time and resources, the implementation and evaluation stages were not carried out. Thus, only the analysis, design, and development stages are carried out. The data collection of this study used a questionnaire method by providing assessment sheets to two media expert lecturers, two Indonesian language material experts, and two first-grade elementary school teachers. The data from the validation results from the experts were then analysed using the mean formula to determine the average score of the validity of the reading learning videos. The analysis results showed that the average score of the validation of the reading learning video was 4.73, and the validation of the material was 4.81. Based on the results of this analysis, the reading learning video for first-grade students of elementary school was declared valid and had very good criteria.